"There's Something Not Right" and "Bringing it Forward": Identifying and Responding to Clinical Challenges. (July 2015) - Heiden-Rootes, Katie M.; Jones, Ariel N. Hooker; Reddick, Geoffrey T.; Jankowski, Peter J.; Maxwell, Kelly
Modified grounded theory method was utilized to explore the process of how clinicians defined and chose to respond to challenging issues in systemic therapy. Defining an issue as challenging was determined by negotiating internal and external cues and "bringing it forward" and "slowing the pace" emerged as key themes in responding to challenging issues. Clinicians appeared to focus on in-session relational process over content, attending to internal aspects of themselves and their interaction with clients and then negotiating those aspects of awareness with their clients. Practice implications are focused on supervision and helping postgraduate clinicians move toward the developmental stage of experienced professionals.